Green purchase intention among Universiti Teknologi MARA Kampus Bandaraya Melaka student / Zamnuri Zaifudin - Zaifudin, Zamnuri (Faculty of Business and Management, 2019)
Green purchasing alludes to reusing, obtaining and utilizing environment friendly items that have negligible harm to the environment. This study inspects relationship between elements that influence the green purchase intentions among undergraduates in Universiti Teknologi MARA Kampus Bandaraya Melaka (UiTM KBM). The study canters on the three noteworthy independent variables got from writing including self-image, environmental concern and social influence on the dependent variable green purchase intention. This study target respondent was UiTM KBM undergraduates and the sample are green consumer. Meanwhile, 100 personal administered were distributed to the respondent. The study utilized descriptive study concept and used nonprobability convenience sampling design. All data recorded from the questionnaire were analysed using Statistical Packaged for Social Science version 22. The measurable investigation of the information mirrors that environmental concern and self-image impacts green buying aim where as social Influence don't influence green purchase intention of consumer.